The Relationship Between Sleep Patterns and Physical Activity with Changes in Blood Pressure Among Hypertensive Patients - Audrey Meidina Iraini; Ribka Sabrina Panjaitan; Rizqa Wahdini (Jurnal Keperawatan Profesional, 2026)
Hypertension is one of the chronic health problems that remains a major concern in Indonesia. This condition is often influenced by lifestyle factors, such as irregular sleep patterns and lack of physical activity, which can elevate blood pressure and worsen cardiovascular function. This study aims to examine the relationship between sleep patterns and physical activity with changes in blood pressure. A quantitative approach with a cross-sectional design was used. The sample consisted of hypertensive patients aged ≥18 years, selected using a simple random sampling technique. Research instruments included the Pittsburgh Sleep Quality Index (PSQI), the Global Physical Activity Questionnaire (GPAQ), and a blood pressure monitor. Data were analyzed using the chi-square test. Results showed that 51.6% of respondents had good sleep quality, while 48.4% had poor sleep quality; 60% engaged in light physical activity and 40% in moderate activity. A highly significant relationship was found between sleep patterns and physical activity with changes in blood pressure (p=0.000). Conclusion: Sleep patterns and physical activity significantly affect blood pressure. These findings can serve as a foundation for health promotion programs at community health centers to encourage healthy lifestyle interventions for individuals with hypertension